Burden of micronutrient deficiency among patients with type 2 diabetes: systematic review and meta-analysis - Sanjay Kalra; Shiv Dutt Gupta; Daya Krishan Mangal; Diksha Gautam; Anuj Kumar Pandey; Nida Shaikh; Himanshu Tolani; Yeshwanth Sonnathi; Kamlesh Chand Sharma; Jagdish Prasad; Rajeev Tewari; Fahmina Anwar (BMJ Nutrition, Prevention & Health)
Background Micronutrient deficiencies are a significant issue worldwide, particularly in South Asia and sub-Saharan Africa. These deficiencies can impact glucose metabolism and insulin signalling pathways, potentially leading to the beginning and advancement of type 2 diabetes (T2D). This study is a comprehensive assessment of the burden of multiple micronutrient deficiencies among T2D patients. The aim of the study is to resolve conflicting evidence from previous studies that mainly focused on one specific micronutrient.Methods The systematic review followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) 2020 guidelines and the Cochrane Handbook. This comprehensive literature search explored Embase, ProQuest, PubMed, Scopus, Cochrane Library, Google Scholar, LILACS and the grey literature, and studies that met the inclusion criteria. A pre-piloted data extraction sheet was used to extract data for relevant study outcomes and characteristics. Results were produced by R V.4.3.2 (R Core Team 2023 using general packages such as tidyverse, and specific packages such as meta and metafor.Results The analysis included 132 studies with 52 501 participants. The pooled prevalence of multiple micronutrient deficiency (vitamins, minerals and electrolytes) was 45.30% (95% CI 40.35% to 50.30%) among T2D patients. The pooled prevalence (48.62%, 95% CI 42.55 to 54.70) was higher in women with T2D than in men. Vitamin D was the most prevalent micronutrient deficiency (60.45%, 95% CI 55% to 65%), followed by magnesium (41.95%, 95% CI 27% to 56%). B12 deficiency (28.72%, 95% CI 21.08% to 36.37%) was higher in the metformin consuming group. The prevalence of micronutrient deficiency varied across WHO regions.Conclusions Micronutrient deficiencies were common in T2D patients, the most common being vitamin D deficiency. Women were more likely to be affected by micronutrient deficiency than men. These studies were hospital based and the findings of this systematic review may be used with caution due to inherent selection bias. Diversity of foods, lifestyle choices and cultural practices may contribute to geographic variations in micronutrient deficiency.Trial registration PROSPERO CRD42023439780.